Non-equilibrium metal oxides via reconversion chemistry in lithium-ion batteries - Xiao Hua (Nature Portfolio, 2021)
The charging of Fe and Mn oxide anodes in lithium-ion batteries are believed to form rocksalt phases via reconstructive conversion reactions. Here, the authors show that M x O y (M = Fe, Mn) transform into non-native body-centred cubic FeO and zincblende MnO via topotactic displacement-like pathways.